Peran Inovasi dalam Total Quality Management dan Kinerja Organisasi - Rina Yuniarti (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
The purpose of this study was to determine the effect of Total Quality Management (TQM) on organizational performance mediated by innovation. This study used primary data in the form of a questionnaire to test the existing hypotheses and analyzed using the Structural Equation Model (SEM). The sample in the study amounted to 203 SMEs in Bengkulu City. Data were analyzed using descriptive statistical analysis using WarpPLS software version 6.0. The results showed that: (1). Total Quality Management has a significant positive effect on organizational performance. (2). Innovation does not mediate the effect of Total Quality Management on organizational performance.